2018
DOI: 10.7150/ijms.24605
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bone Marrow-Derived Cells during Ectopic Bone Formation of Mouse Femoral Muscle in GFP Mouse Bone Marrow Transplantation Model

Abstract: Multipotential ability of bone marrow-derived cells has been clarified, and their involvement in repair and maintenance of various tissues has been reported. However, the role of bone marrow-derived cells in osteogenesis remains unknown. In the present study, bone marrow-derived cells during ectopic bone formation of mouse femoral muscle were traced using a GFP bone marrow transplantation model. Bone marrow cells from C57BL/6-Tg (CAG-EGFP) mice were transplanted into C57BL/6 J wild type mice. After transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In another study, no transplanted human BMSC could be detected in ectopic mouse transplants beyond 2 weeks, despite robust bone formation at 8 weeks (Gamblin et al, 2014). These reports further suggest that transplanted BMSC contribute to bone formation via stimulation of tissue-resident progenitor cells rather than direct differentiation into osteoblasts (Tsujigiwa et al, 2013;Takabatake et al, 2018). Indeed, the type and immune status of the animal-model may also influence in vivo osteogenesis (Garske et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, no transplanted human BMSC could be detected in ectopic mouse transplants beyond 2 weeks, despite robust bone formation at 8 weeks (Gamblin et al, 2014). These reports further suggest that transplanted BMSC contribute to bone formation via stimulation of tissue-resident progenitor cells rather than direct differentiation into osteoblasts (Tsujigiwa et al, 2013;Takabatake et al, 2018). Indeed, the type and immune status of the animal-model may also influence in vivo osteogenesis (Garske et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have characterized the role of exogenous cells in ectopic and orthotopic bone formation. For example, transplantation of allogeneic BMSC in immunocompetent mice revealed immune modulation rather than osteoblastic differentiation in one study ( Tsujigiwa et al, 2013 ; Takabatake et al, 2018 ). In another study, no transplanted human BMSC could be detected in ectopic mouse transplants beyond 2 weeks, despite robust bone formation at 8 weeks ( Gamblin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that osteoclasts develop through the fusion of monocyte precursors derived from HSCs in the presence of M-CSF and RANKL [ 28 , 29 ]. In contrast, it is difficult for osteoblasts or bone cells to colonize the bone marrow through bone marrow transplantation [ 30 ]. If the bone mass changes in Bhlhe40 −/− mice are dominated by osteoblasts or other bone cells, the phenotype of the recipient mice should depend on themselves rather than the donors.…”
Section: Discussionmentioning
confidence: 99%
“…To verify if there are any altered response of GFP transgenic mice to TBI, a mouse model for RAR (Yonezawa Effect) was adopted and applied to this work using C57BL/6N-GFP mice, the first engineered GFP transgenic mice in the world with applications in a wide range of research fields including radiation biology. 25 , 51 - 63 RAR is a phenomenon that pre-exposure to a low priming dose reduces the biological effects of a subsequent higher challenge dose. Since the discovery of RAR, 64 it has been demonstrated in a variety of biosystems from simple prokaryotes to higher eukaryotes including mammalian animals with varied endpoints including cell death and bone marrow death.…”
Section: Discussionmentioning
confidence: 99%